Cocopeat: An alternative to soil medium for propagation of papaya (Carica papaya L) - Gowthami, Kakarla; Vidhya, D; Muthuvel, I; Djanaguiraman, M; Jagadeeswaran, R (Plant Science Today, 2024)
The present study aimed to standardize soilless media mixtures for papaya propagation, focusing on stability, sustainability and environmental impact. A trial was conducted in the winter and summer seasons during 2023-2024 at TNAU, Coimbatore, to evaluate the properties of cocopeat mixtures and optimize the cocopeat media mixture for papaya seedling production. The trial employed a factorial randomized complete block design with two factors [cocopeat media mixture (Factor-T) and papaya varieties (CO7 and TNAU Papaya CO8, as factor-V] and with four replicates. Each treatment contains different proportions of cocopeat, inorganic fertilizers, bio-inoculants, biofertilizers and oil cakes. Commercially available cocopeat and potting mixture were used as absolute control and control, respectively. The findings showed that T2 (TNAU Mixture 2) consist of cocopeat (96.86%) + inorganic mixture (0.34%) + bioinoculant mixture (0.70%) + biofertilizer mixture (0.42%) + oil cakes mixture (0.42%) recorded increased seed vigour (96.86%), seedling survival (96.17%), seedling height (46.07 cm), leaf area/plant (28.50 cm²), leaf chlorophyll (26.05 SPAD units) and total nutrient (N-1.89%, P-0.89%, K-3.47%). The treatment T4 (commercially available cocopeat alone) had the highest germination (97.90%) and was on par with T2. Among the variety, V2 outperformed V1. In the treatment (T) and variety (V) interaction, the T2×V2 combination promoted significant seedling growth at the nursery. Cocopeat media mixtures showed good physical properties, like bulk density(g/cc), particle density (g/cc), porosity (%) and water holding capacity (%), promoting better seedling growth. The trial revealed that the treatment T2 is recommended as the best alternative soilless medium for papaya propagation.